Jurnal Pengalaman Komunikasi Mahasiswa Generasi Sandwich (Stusi Fenomenologi Pada Mahasiswa Di Kabupaten Karawang) - Kinantika, Maya Linanda Indriani; Tayo, Siti Nursanti, Yanti (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research uses qualitative methods and a phenomenological approach, because in this study we want to find out a phenomenon that comes from the direct experience of the informants, and also want to know its meaning and motives. The theory used in this study is Alfred Schutz's Phenomenological Theory which is the basis for researchers in carrying out this research. The results of the study show that first, the motives for students choosing to be the sandwich generation are due to economic factors and family factors. Then the motive for (in-order-to motive) is to increase income, fill time, family demands, and achieve desires. Second, interpreting sandwich generation students as paying tuition fees and helping parents, experience and special roles, family demands, and career support. Third, communication experiences are divided into two categories, namely positive communication experiences such as good treatment from family, and support from friends. While the negative communication experience gained is not supported by family and belittled by friends.